Estudio comparativo entre el diseño curricular del área de inglés por grados en la Institución Educativa Ofelia Velásquez y por niveles en la Institución Educativa Virgen Dolorosa de la provincia de San Martín en el año 2011 - Arce Saavedra, Boris Jesus (2012)
The purpose of this research is to understand the differences between the English Area Curriculum Design by Grades in Ofelia Velasquez High School and the English Area Curriculum Design by Levels in Virgen Dolorosa High school respectively, in the Department of San Martin in 2011. To achieve this purpose, information from these two English Curriculum Designs using census-type was gathered; documents as curriculum proposals, annual programs, learning unites and different lesson plans, as well as, a sample of 50 students from each schools and a total of 5 teachers (3 of them from Ofelia Velasquez High school and 2 from Virgen Dolorosa High school) were interviewed and observed. Research tools, such as Observation sheets, Surveys and lnterview guides were elaborated, validated and applied, then., the tabulation of data, descriptions and a strict analysis were done; finally, the results of this research tools were compared in both Curriculum Design cases having in consideration the dimensions in the consistency matrix research. The results showed that there are differences in the performance of both Curriculum Designs indeed, having more significant differences in the dimensions of Methodology and Contents.